Opposing Power : Building Opposition Alliances in Electoral Autocracies - Ong, Elvin Jiayun, 1985- (Book collections on Project MUSE., 2022)
"When do opposition party leaders build pre-electoral alliances to compete against electoral autocrats? Through two pairs of case study comparisons in East and Southeast Asia-between the Philippines and South Korea in the late 1980s, and between Malaysia and Singapore from 1965 to 2020-Opposing Power argues that opposition elites' perceptions of regime vulnerability and mutual dependency shape their efforts to construct alliances. Multiple regime-debilitating events striking the incumbent within a short period of time can raise opposition expectations of impending victory, galvanizing efforts for inter-party coordination. Clear information about the relative strengths and weaknesses of opposition parties fosters recognition of their mutual dependency, inducing party leaders to coordinate towards joint victory. Drawing on a broad range of archival material and a wealth of fieldwork, Opposing Power illustrates how dueling opposition parties can sometimes become strange bedfellows."